ASSESSMENT OF ANTIOXIDATIVE AND AMELIORATIVE POTENTIAL OF AQUEOUS EXTRACT OF LEAVES OF THUJA ORIENTALIS (PLATYCLADUS ORIENTALIS [L.]) - Mehra, Sukanya; Sharma, Shelly; Chadha, Pooja (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The main objective of the present study is to assess the antioxidative and attenuating potential of aqueous extract of leaves of Thuja orientalis (AET) against the genotoxicity induced by chlorpyrifos (CPF) (O,O-diethyl O-(3,5,6-trichloro-2-pyridyl) phosphorothioate). Methods: Phytochemical analysis of the extract was performed to reveal the presence of various bioactive compounds. Free radical scavenging activity was assessed using 2, 2-diphenyl-1-picrylhydrazyl (DPPH) assay and further genoprotective activity of AET was evaluated by in vivo studies using rat as model. For this purpose, male healthy rats, 8–10 weeks old, weighing 120±10 g, were selected and divided into three groups, namely Group 1 fed with corn oil, taken as control, Group 2 fed with CPF, and Group 3 treated with AET 1 week before CPF exposure. ¼ of LD50, i.e., 38 mg/kg CPF was used for experiment and was orally administered to rats. Results: The presence of bioactive compounds such as saponins, alkaloids, flavonoids, and terpenes was confirmed by phytochemical analysis. DPPH assay revealed the IC50 value which was deduced to be 205.04 μl/ml. In vivo study including exposure to pesticide alone for 24 h, 48 h, and 72 h showed significant increase in DNA damage (p≤0.01) in liver, kidney, and blood as compared to control. However, a dose of AET 400 mg/kg p.o. given 1 week before each duration of CPF exhibited significant protection from CPF-induced genotoxicity. Conclusion: Thus, the study suggests the positive effect of aqueous leaf extract of T. orientalis in ameliorating the damage induced by pesticide exposure.